Evaluating the in vitro therapeutic effects of human amniotic mesenchymal stromal cells on MiaPaca2 pancreatic cancer cells using 2D and 3D cell culture model. (February 2021) - Rahmani, Zahra; Safari, Fatemeh
Graphical abstract: Highlights: hAMSCs have inhibitory effects on cancer cells using 2D and 3D cell culture systems. Abstract: Human amniotic mesenchymal stromal cells (hAMSCs) are considered as a population of multipotent cells. The molecular events associated with mesenchymal stromal cell (MSC)/tumor cell interactions should be studied to identify the role of MSCs on suppressing or inducing the key signaling pathways of tumor cells. Thus, designing therapeutic approaches is considered as important. In the present study, hAMSCs and MiaPaca2 cells were first cultured separately. In addition, both cell lines were co-cultured by using 0.4 μm pore sized transwell membranes in different times. Further, the RNA of the cells was extracted, and Bcl2, Bax, epidermal growth factor receptor (EGFR), c-Src, C-terminal Src Kinase (CSK), and SGK223 expression were analyzed through quantitative real time PCR. Furthermore, the total cell lysates of the cells were prepared and analyzed by using western blot. Based on the results, the expression of EGFR, c-Src, SGK223, and CSK in MiaPaca2 cells reduced after treating with hAMSCs. Notably, the cellular apoptosis of MiaPaca2 cells was induced in 2D cell culture system. Further, the anti-cancer activity of conditioned medium from hAMSCs was confirmed in a 3D cell culture model by using hanging drop technique. Finally, hAMSCs have inhibitory effects on pancreatic cancer cells and can be considered as a therapeutic way to suppress EGFR, c-Src, and SGK223, as the potent targets in cancer cell signaling.